ANALISIS PROFITABILITAS PADA PT BFI FINANCE INDONESIA - Tumiwa, Aiden; Tampi, J. R. E.; Sambul, S. A. P. (Sam Ratulangi University, 2016)
ABSTRACT Profitability is ratio to asses the companyâ€™s to make profit. Financialratio is the number of points gained from the comparison of the financial statementitems with more posts.Â The research technique using quantitative descriptive analysis, to determinethe profitability. Based on research results from 2012 to 2014 has increased anddecreased, using profitability analysis, that is Net Profit Margin, Return onInvestmen and Return on Equity.Â Although the decline and below the industry standard, PT. BFI FinanceIndonesia Tbk, fixed Profit.Keywords : Financial Ratio, Profitability